Answer to Question #4424 in Real Analysis for sachin sharma
first if x<-1 then we can rewrite equation -x-1-x+2=7 so
-2x=6& we have x=-3 and it is <-1 so it is solution.
then we rewrite equation x+1+2-x=7 3=7 so there is no solution in this
third x>2 so x+1+x-2=7 2x-1=7& 2x=8 x=4>2
so we have two
solutions x=-3, x=4
You're welcome. We are glad to be helpful.
If you really liked our service please press like-button beside answer field. Thank you!
Thank u so much
You are welcome. We were pleased to help you
thank you very much